Morphological plasticity in the Aristotle’s lantern of Arbacia dufresnii (Phymosomatoida: Arbaciidae) off the Patagonian coast - Epherra, Lucía (2015)
The relative size of the Aristotle’s lantern of most sea urchins varies in relation to the food availability and it is often used to infer the availability of food of the environment. The aim of our study was to evaluate the lantern morphology plasticity of Arbacia dufresnii in populations with different environmental characteristics, either mussel beds or disturbed areas, by the invasive alga Undaria pinnatifida along the Patagonian Atlantic coast. The test diameter of the sea urchins along with the weight and height of the lanterns, the jaw lenght and rotula lenght were measured. Classic and geometric morphometric analyses were performed to test differences among populations. The length of the jaw was the best indicator of relative changes in size of the lantern. The largest length of the jaw was measured in individuals from disturbed areas dominated by the invasive algae U. pinnatifida. The rotula shape changed with the increase of the diameter of the sea urchins, it tends to be more elongated with larger sea urchins.